New Strategies to Promote Macrophage Cholesterol Efflux - Choi, Hong Y.; Ruel, Isabelle; Choi, Shiwon; Genest, Jacques (Frontiers in Cardiovascular Medicine, 2021)
The capacity of macrophages to dispose of cholesterol deposited in the atherosclerotic plaque depends on their ability to activate cholesterol efflux pathways. To develop athero-protective therapies aimed at promoting macrophage cholesterol efflux, cholesterol metabolism in THP-1 monocyte-derived macrophages has been extensively studied, but the intrinsic sensitivity of monocytes and the lack of a standardized procedure to differentiate THP-1 monocytes into macrophages have made it difficult to utilize THP-1 macrophages in the same or similar degree of differentiation across studies. The variability has resulted in lack of understanding of how the differentiation affects cholesterol metabolism, and here we review and investigate the effects of THP-1 differentiation on cholesterol efflux. The degree of THP-1 differentiation was inversely associated with ATP-binding cassette A1 (ABCA1) transporter-mediated cholesterol efflux. The differentiation-associated decrease in ABCA1-mediated cholesterol efflux occurred despite an increase in ABCA1 expression. In contrast, DSC1 expression decreased during the differentiation. DSC1 is a negative regulator of the ABCA1-mediated efflux pathway and a DSC1-targeting agent, docetaxel showed high potency and efficacy in promoting ABCA1-mediated cholesterol efflux in THP-1 macrophages. These data suggest that pharmacological targeting of DSC1 may be more effective than increasing ABCA1 expression in promoting macrophage cholesterol efflux. In summary, the comparison of THP-1 macrophage subtypes in varying degrees of differentiation provided new insights into cholesterol metabolism in macrophages and allowed us to identify a viable target DSC1 for the promotion of cholesterol efflux in differentiated macrophages. Docetaxel and other pharmacological strategies targeting DSC1 may hold significant potential for reducing atherogenic cholesterol deposition.